Livelihood assessment: A participatory tool for natural resource dependent communities - Jutta Lax; Joachim Krug (Johann Heinrich von Thünen-Institut, 2013)
[Foreword] Globally, around 15 million hectares of forests - mainly tropical forests - are converted to other uses or lost through natural causes each year. Without forests mankind has no chance to survive. However, the poorest of the poor are directly dependent on forests as a resource of food, medicine, construction material and energy. Management, conservation, and sustainable development of forests are key issues of the international environmental and forest policy since the United Nations Conference on Environment and Development in Rio de Janeiro in the year 1992 to counteract the destruction of forests. In order to maintain tropical forests and to conserve their functions, structure and biodiversity as a collective good of humankind, forests need to be managed in a sustainable way. Conservation efforts are faced with the threefold task of incorporating ecological, economic and social sustainability aspects equally into development approaches. The relevance of livelihood issues to sustainable development has its basis in the United Nations Conference on Environment and Development 1992 and is at present an essential element in development approaches (e.g. MDGMillenium Development Goals). In line with Campbell the understanding of rural livelihoods is one of the keys to putting an end to global poverty. Though environmental resources can make up a considerable proportion of rural livelihoods it is necessary to evaluate this environmental dependency. This field manual introduces a participatory tool for the assessment of local livelihood situations of rural forest dependent communities. The assessment tool was initially implemented in a case study in Northern Vietnam. Vietnam, representative for many other tropical countries considered a developing country, where over 60 % of the population's livelihood strategy is based on agricultural and forest activities.
urn:nbn:de:gbv:253-201308-dn052272-8
Keywords: 630